Dual Targeting of DNA Damage Response Proteins Implicated in Cancer Radioresistance - Vasilopoulos, Spyridon N.; Guner, Hueseyin; Apaydin, Merve Uca; Pavlopoulou, Athanasia; Georgakilas, Alexandros G.; Uça Apaydın, Merve (MDPI, 2023)
Ionizing radiation can induce different types of DNA lesions, leading to genomic instability and ultimately cell death. Radiation therapy or radiotherapy, a major modality in cancer treatment, harnesses the genotoxic potential of radiation to target and destroy cancer cells. Nevertheless, cancer cells have the capacity to develop resistance to radiation treatment (radioresistance), which poses a major obstacle in the effective management of cancer. It has been shown that administration of platinum-based drugs to cancer patients can increase tumor radiosensitivity, but despite this, it is associated with severe adverse effects. Several lines of evidence support that activation of the DNA damage response and repair machinery in the irradiated cancer cells enhances radioresistance and cellular survival through the efficient repair of DNA lesions. Therefore, targeting of key DNA damage repair factors would render cancer cells vulnerable to the irradiation effects, increase cancer cell killing, and reduce the risk of side effects on healthy tissue. Herein, we have employed a computer-aided drug design approach for generating ab initio a chemical compound with drug-like properties potentially targeting two proteins implicated in multiple DNA repair pathways. The findings of this study could be taken into consideration in clinical decision-making in terms of co-administering radiation with DNA damage repair factor-based drugs.
Pavlopoulou, Athanasia/0000-0002-0815-3808; Georgakilas, Alexandros/0000-0002-5971-0010; Vasilopoulos, Spyridon/0009-0007-0596-2945; Guner, Huseyin/0000-0002-0220-5224
Keywords: Radiation Therapy; Radiation Resistance; DNA Damage Repair; Computer-Aided Drug Design; Dual Targeting; Molecular Dynamics